The response of potato (Solanum tuberosum L) to the fungus Rhizoctonia solani - Raikar, S.V.; Shah, F.A.; Pitman, A.R.; Jacobs, J.M.E. (New Zealand Plant Protection, 2010)
Rhizoctonia solani is a soilborne fungal pathogen of many economically important crops Thirteen closely related anastomosis groups (AGs) of this pathogen have been identified each of which affects different plant species Previous studies have suggested that R solani AG3 is the main cause of disease in potato Rhizoctonia solani infection of potato plants can result in stem canker and tubers with black scurf Affected plants give a reduced yield while affected tubers are considered to have reduced quality resulting in economic loss The current study investigated the response of different potato cultivars and lines to R solani AG3 Thirtytwo potato cultivars/lines many actively used in the Plant Food Research potato breeding programme were screened in a shadehouse pot trial The trial was laid out in an adapted resolvable block design to ensure uniform exposure to environmental factors Each cultivar had six replicates four with and two without AG3 inoculum Plants were grown to maturity and the resulting tubers were assessed for disease (black scurf) Preliminary results show that none of the lines/cultivars tested were resistant but degrees of susceptibility varied In this experiment stem canker was not observed in any of the lines/cultivars